Frequency of Hypokalemia, Clinical Implications and Risk Factors in Patients of COVID-19 - Sarmad Zahoor; Uzma Malik; Malik Muhammad Atif; Sadia Asif; Aleena Khan; Sumera Hanif; Ibrar Rafique; Muhammad Arif Nadeem Saqib (Pakistan Journal of Medical Research, 2024)
Objective: To determine the frequency of hypokalemia among COVID-19 patients and assess its impact on the patients management.